Late-stage functionalisation of peptides on the solid phase by an iodination-substitution approach [research data] - Werner, Marius; Pampel, Julius; Pham, Truc Lam; Thomas, Franziska (Universität, 2022)
The functionalisation of peptides at a late synthesis stage holds great potential, for example, for the synthesis of peptide pharmaceuticals, fluor...